Alterations in Mesenteric Lymph Node T Cell Phenotype and Cytokine Secretion are Associated with Changes in Thymocyte Phenotype after LP-BM5 Retrovirus Infection - Maria C. Lopez; Ronald R. Watson (Clinical and Developmental Immunology)
In this study, mouse MLN cells and thymocytes from advanced stages of LP-BM5 retrovirus infection were studied. A decrease in the percentage of IL-7+ cells and an increase in the percentage of IL-16+ cells in the MLN indicated that secretion of these cytokines was also altered after LP-BM5 infection. The percentage of MLN T cells expressing IL-7 receptors was significantly reduced, while the percentage of MLN T cells expressing TNFR-p75 and of B cells expressing TNFR-p55 increased. Simultaneous analysis of surface markers and cytokine secretion was done in an attempt to understand whether the deregulation of IFN-Υ secretion could be ascribed to a defined cell phenotype, concluding that all T cell subsets studied increased IFN-Υ secretion after retrovirus infection. Finally, thymocyte phenotype was further analyzed trying to correlate changes in thymocyte phenotype with MLN cell phenotype. The results indicated that the increase in single positive either CD4+CD8- or CD4- CD8+ cells was due to accumulation of both immature (CD3- ) and mature (CD3+) single positive thymocytes. Moreover, single positive mature thymocytes presented a phenotype similar to the phenotype previously seen on MLN T cells. In summary, we can conclude that LP-BM5 uses the immune system to reach the thymus where it interferes with the generation of functionally mature T cells, favoring the development of T cells with an abnormal phenotype. These new T cells are activated to secrete several cytokines that in turn will favor retrovirus replication and inhibit any attempt of the immune system to control infection.